PENINGKATAN KUALITAS PENGELOLAAN DAN PRODUKTIVITAS UKM PADA KELOMPOK PEMBATIK DESA PLANA DAN SOKAWERA KECAMATAN SOMAGEDE KABUPATEN BANYUMAS - Aldila Krisnaresanti; Nurul Hidayat; Viviana Mayasari; Sri Lestari (Universitas Jenderal Soedirman, 2019)
The target audience of the IbM PPM batik is batik artisans belonging to Group Batik Sekar Geang which 11 members and Group Batik Capit Urang which had 15 members. The emergence of this group is driven by huge demand for batik products in District Somagede and in Banyumas generally unserved as many as 6457 people from school children, teachers and officials in the District Somagede environment. The high school student, a teacher, an employee in the District Somagede in particular and Banyumas generally required to wear batik clothes 2-3 days a week. The size of the potential market is still coupled with the program to realize the integrated tourism in the District Somagede thus requiring a superior product to be used as a souvenir. The main problem is the absence of partners the division of tasks within the group. All members of the group working on production activities, there is no division of labor within the group, no member whose job is to market their products, partners do not perform registration activities group administration in an orderly manner, there has been no attempt of a group to promote their products to the public, are not familiar with marketing on -line for batik products, lack of capital and production equipment to run its business, does not have the skills and equipment to produce batik printing highly prospective for serving uniform school children, teachers and staff in the District Somagede, Design batik motif both partners is still limited and yet varied, packaging and label design is still very modest, small business management capabilities are limited and not yet standardized bookkeeping.Target activities IbM are increased capability partner in the management and administration of the group, the results of administrating the group's activities, a system of division of labor, an increase in sales, marketing services on-line, the design of new batik, batik printing, packaging and labeling of products with attractive design, report financial groups, and scientific journals. To achieve the objectives and outcomes, activities such as counseling, practice, support. The evaluation method by comparing the level of knowledge and ability as well as the performance of the production and marketing partners before and after the activities IbM.